Going to Strasbourg : an oral history of sexual orientation discrimination and the European Convention on Human Rights - Johnson, Paul (Paul James) (Oxford : Oxford University Press, 2016)
A unique study of the role of the European Convention on Human Rights in eradicating discrimination and establishing legal equality on the grounds of sexual orientation in the United Kingdom, containing nineteen oral history accounts of applicants, legal professionals and campaigners.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2016).
Keywords: Homophobia -- Great Britain -- Case studies; Homophobia -- Law and legislation -- Europe -- Cases; Discrimination -- Law and legislation -- Europe -- Cases; Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Politics and Government; Politics & government